Oral Administration of Glutathione Trisulfide Increases Reactive Sulfur Levels in Dorsal Root Ganglion and Ameliorates Paclitaxel-Induced Peripheral Neuropathy in Mice - Mariko Ezaka; Eizo Marutani; Yusuke Miyazaki; Eiki Kanemaru; Martin K. Selig; Sophie L. Boerboom; Katrina F. Ostrom; Anat Stemmer-Rachamimov; Donald B. Bloch; Gary J. Brenner; Etsuo Ohshima; Fumito Ichinose (MDPI AG, 2022)
Peripheral neuropathy is a dose-limiting side effect of chemotherapy with paclitaxel. Paclitaxel-induced peripheral neuropathy (PIPN) is typically characterized by a predominantly sensory neuropathy presenting with allodynia, hyperalgesia and spontaneous pain. Oxidative mitochondrial damage in peripheral sensory neurons is implicated in the pathogenesis of PIPN. Reactive sulfur species, including persulfides (RSSH) and polysulfides (RSnH), are strong nucleophilic and electrophilic compounds that exert antioxidant effects and protect mitochondria. Here, we examined the potential neuroprotective effects of glutathione trisulfide (GSSSG) in a mouse model of PIPN. Intraperitoneal administration of paclitaxel at 4 mg/kg/day for 4 days induced mechanical allodynia and thermal hyperalgesia in mice. Oral administration of GSSSG at 50 mg/kg/day for 28 days ameliorated mechanical allodynia, but not thermal hyperalgesia. Two hours after oral administration, 34S-labeled GSSSG was detected in lumber dorsal root ganglia (DRG) and in the lumber spinal cord. In mice treated with paclitaxel, GSSSG upregulated expression of genes encoding antioxidant proteins in lumber DRG, prevented loss of unmyelinated axons and inhibited degeneration of mitochondria in the sciatic nerve. In cultured primary neurons from cortex and DRG, GSSSG mitigated paclitaxel-induced superoxide production, loss of axonal mitochondria, and axonal degeneration. These results indicate that oral administration of GSSSG mitigates PIPN by preventing axonal degeneration and mitochondria damage in peripheral sensory nerves. The findings suggest that administration of GSSSG may be an approach to the treatment or prevention of PIPN and other peripheral neuropathies.